2017
DOI: 10.1515/jpm-2016-0099
|View full text |Cite
|
Sign up to set email alerts
|

Fourfold increase in prevalence of gestational diabetes mellitus after adoption of the new International Association of Diabetes and Pregnancy Study Groups (IADPSG) criteria

Abstract: The adoption of the IADPSG criteria resulted in a considerable increase in GDM diagnosis in our Swiss cohort. Further studies are needed to investigate if the screening is cost effective and if treatment of our additionally diagnosed GDM mothers might improve short-term as well as long-term outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 20 publications
0
26
0
4
Order By: Relevance
“…The reported figure for frequency of GDM goes in hand with Ma et al (30) , Karcaaltincaba et al (31) and Arbib et al (32) who reported frequencies of 12.2%, 11.1% and 9.9%, respectively for GDM. Moreover, Huhn et al (33) and Brown & Wyckoff (34) documented that the introduction of the IADPSG criteria resulted in an absolute increase of GDM prevalence of 8.5% (33) and a 1.03-3.78-fold rise versus baseline criteria (34) .…”
Section: Discussion:-mentioning
confidence: 99%
“…The reported figure for frequency of GDM goes in hand with Ma et al (30) , Karcaaltincaba et al (31) and Arbib et al (32) who reported frequencies of 12.2%, 11.1% and 9.9%, respectively for GDM. Moreover, Huhn et al (33) and Brown & Wyckoff (34) documented that the introduction of the IADPSG criteria resulted in an absolute increase of GDM prevalence of 8.5% (33) and a 1.03-3.78-fold rise versus baseline criteria (34) .…”
Section: Discussion:-mentioning
confidence: 99%
“…The prevalence of GDM diagnosed by IADPSG criteria has been reported as 17.6%, 4.2%, 11.8%, 9.5%, 23.3%, 8.6%, and 45% in Singapore, Greenland, Switzerland, South Korea, Sri Lanka, Sub‐Saharan Africa, and the United Arab Emirates, respectively. By contrast, a two‐step approach for diagnosis determined a GDM prevalence of 3.3% in Switzerland and 12% in the United Arab Emirates . This approximately fourfold increase in prevalence of GDM determined by the IADPSG criteria is similar to the present findings.…”
Section: Discussionmentioning
confidence: 99%
“…Consultation of the case history indicated that this pregnant woman had been diagnosed with GDM at the time of blood sampling [19]. GDM is a unique form of glucose intolerance, being of a transient nature and only occurring during pregnancy in women with no prior history of diabetes [68][69][70]. GDM shares a number of features in common with T2DM, such as a systemic inflammation associated with the metabolic syndrome.…”
Section: Infiltrating Pmn Alter Placental Function In Gdm Via the Actmentioning
confidence: 99%